The relationship between platelet reactivity and infarct-related artery patency in patients presenting with a ST-elevation myocardial infarction - Breet, Nicoline J; van Werkum, Jochem W; Bouman, Heleen J; Kelder, Johannes C; Hackeng, Christian M; ten Berg, Jurriën M (Thrombosis and haemostasis, 2011)
Both heightened platelet reactivity and an occluded infarct related artery (IRA) on initial angiography and at the time of primary percutaneous coronary intervention (PCI) are associated with a worsened clinical outcome in patients with ST-elevation myocardial infarction (STEMI). However, the relationship between platelet reactivity and IRA patency has not yet been established. Consecutive STEMI-patients were enrolled in this study. Patients who had TIMI-flow (thrombolysis in myocardial infarction) 0 or 1 on initial angiography constituted the occluded IRA group and patients having TIMI-flow 2 or 3 comprised the IRA patent group. Platelet function measurements were performed using the PFA-100 COL/ADP cartridge and light transmittance aggregometry without agonist (spontaneous) and after stimulation with adenosine diphosphate (ADP) and arachidonic acid (AA). Ninety-nine patients were enrolled, of whom 49 presented with an occluded IRA. Multivariate analysis identified the following independent factors to be associated with an occluded IRA; short COL/ADP closure time (ORper quartile increase=0.60; 95% CI, 0.39-.93; p=0.02), the 20 μM ADP-induced light transmittance aggregometry (ORper quartile increase =1.77; 95% CI, 1.15-2.73; p=0.01) and leukocyte counts (odds ratio [OR]=1.21; 95% CI, 1.05-1.39; p = 0.008). In conclusion, heightened platelet reactivity and elevated leukocyte counts are associated with an occluded IRA upon presentation in STEMI-patients. These results emphasise the importance of potent antithrombotic therapy early after the onset of symptoms, to obtain early recanalisation of the IRA.